PROBLEMS OF IMPLEMENTATION AND HARMONIZATION OF INDIVIDUAL AND CORPORATE INTEREST - D. Gurov; N. Gotskay (Вестник университета, 2016)
Discusses the issue of coordination of interests of participants of economic activities. The designated subjects of the market relations that serve as the basis for the implementation of the market transactions, which are implemented and economic interests, both individual and corporate. The main condition of market making transactions and the realization of the economic interests of both parties - the empowerment of the subjects of the market relations of ownership. Confrontation and negotiation of individual and corporate interests lead to a functioning equilibrium of the market in conditions of free competition. Indicate the objective necessity of the practical use of economic studies to enhance the activity of economic activity of people.